List Scheduling in Embedded Systems under Memory Constraints - Arras, Paul-Antoine; Fuin, Didier; Jeannot, Emmanuel; Stoutchinin, Arthur; Thibault, Samuel (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2013: Anais do XXV International Symposium on Computer Architecture and High Performance Computing, 2013)
Video decoding and image processing in embedded systems are subject to strong resource constraints, particularly in terms of memory. List-scheduling heuristics with static priorities (HEFT, SDC, etc.) being the often-cited solutions due to both their good performance and their low complexity, we propose a method aimed at introducing the notion of memory into them. Moreover, we show that through appropriate adjustment of task priorities and judicious resort to insertion-based policy, speedups up to 20% can be achieved. Lastly, we show that our technique allows to prevent deadlock and to substantially reduce the required memory footprint compared to classic list-scheduling heuristics.